Kajian Teoritis tentang Pembelajaran Berbasis Proyek (PjBL) untuk Mengembangkan Keterampilan Kolaborasi Siswa MI - Bakar, Abu (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2023)
This study aims to analyze the implementation of Project-Based Learning (PjBL) in developing collaboration skills among students at Madrasah Ibtidaiyah (MI). This is a qualitative research with a case study approach. The research subjects are fifth-grade students at MI Al-Bukhori Pekanbaru, while the research object is the application of PjBL in teaching and the collaboration skills developed in students. Data collection techniques include observation, interviews, and documentation. Data were analyzed using descriptive qualitative analysis. The results show that the application of PjBL enhances students' collaboration skills, such as teamwork, communication, and problem-solving. Although challenges like time limitations and students' social skills exist, teacher support and the use of technology help facilitate PjBL implementation. In conclusion, PjBL is an effective approach to developing students' collaboration skills at MI, with proper adjustment and support from educators.